Switching charge-transfer characteristics from p-type to n-type through molecular “doping” (co-crystallization) - Zhang, Jing (2018)
Borrowing an idea from the silicon industry, where the charge-carrier's characteristics can be changed through heteroatom implantation, we believe that the charge transport nature of organic semiconductors can be switched through molecular “doping” (co-crystallization). Here, we report a novel molecule 2,7-di-tert-butyl-10,14-di(thiophen-2-yl)phenanthro[4,5-abc][1,2,5]thiadiazolo[3,4-i]phenazine (DTPTP), which originally is a p-type (0.3 cm2 V−1 s−1) compound, and can be switched to an n-type semiconductor (DTPTP2–TCNQ, 3 × 10−3 cm2 V−1 s−1 under air conditions) through tetracyanoquinodimethane (TCNQ) doping (co-crystallization). Single crystal X-ray studies revealed that TCNQ-doped DTPTP complexes (DTPTP2–TCNQ) adopt a dense one-dimensional (1D) mixed π–π stacking mode with a ratio of DTPTP and TCNQ of 2 : 1, while pure DTPTP molecules utilize a herringbone-packing pattern. Interestingly, theoretical analysis suggested that there is a quasi-2D electron transport network in this host–guest system. Our research results might provide a new strategy, to switch the charge transport characteristics of an original system by appropriate molecular “doping” (co-crystal engineering).